Analisa Fasilitas Penunjang Event Venue dalam Meningkatkan Kepuasan Pengunjung Konser Musik (Studi Kasus pada Event Venue di Jakarta) - Angelia, Michelle; Widagdyo, Kurniawan Gilang (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2024)
Venue management in music concert organization plays a crucial role in shaping audience experience and determining the success of an event. This study is motivated by the increasing number of music concerts held in the Jabodetabek area and the supporting facilities provided by each venue. Therefore, the main objective of this research is to analyze the impact of event venue supporting facilities on concertgoers' satisfaction levels at several major concert venues in Jabodetabek. This study employs a quantitative approach using multiple regression analysis with Smart PLS. Data were collected through questionnaires distributed to individuals who had attended concerts at major venues, namely Istora Senayan, JIExpo Kemayoran, Gelora Bung Karno Main Stadium (SUGBK), and Jakarta International Stadium (JIS). The findings reveal that supporting facilities, which include general amenities, signage aspects (directional signs), accessibility, and seating layout, do not all significantly influence audience satisfaction levels. The signage aspect and seating layout were found to be the primary factors in creating a positive experience for concertgoers. Meanwhile, general amenities and accessibility did not show a significant impact on the comfort and satisfaction of concert attendees.